1976
DOI: 10.1111/j.1365-2133.1976.tb05135.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular changes in human skin after ultraviolet irradiation

Abstract: Blood-flow changes in human skin after ultraviolet irradiation at 250 and 300 nm have been measured by three separate methods. Those methods which measure overall blood-flow changes in the skin showed increased flow after irradiation at both wavelengths. A method which measured flow only in the superficial vessels showed a slight increase in flow after low doses of both wavelengths, but in contrast, after higher doses, this method showed a marked reduction in flow through the upper dermal vessels. This reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 11 publications
2
22
0
Order By: Relevance
“…Blood flow in non-irradiated and in irradiated skin, before and after oral indomethacin, was dmined by a photoelectric plethysmographic technique (Ramsay & Challoner, 1976).…”
Section: Photoelectricplethysmographic Bloodflow Measurementsmentioning
confidence: 99%
“…Blood flow in non-irradiated and in irradiated skin, before and after oral indomethacin, was dmined by a photoelectric plethysmographic technique (Ramsay & Challoner, 1976).…”
Section: Photoelectricplethysmographic Bloodflow Measurementsmentioning
confidence: 99%
“…30 Increased blood flow changes in human skin following UV irradiation at both 250 and 300 nm have been measured. 31 However, in case of superficial vessels, following low doses of both wavelengths a slight increase in blood flow, and following higher doses, a marked reduction in blood flow was observed. This reduction was attributed to the stasis in these superficial vessels, perhaps, secondary to vascular damage.…”
Section: Discussion Of Findings and Relevant Literaturementioning
confidence: 98%
“…This reduction was attributed to the stasis in these superficial vessels, perhaps, secondary to vascular damage. 31 The keratinocytederived vascular endothelial growth factor (VEGF, also known as VPF or vascular permeability factor) provides the major cutaneous angiogenic activity in epidermal keratinocytes and its overexpression results in hyperpermeable dermal capillaries. 32 34 In a previous study, hypoxia through generation of ROS was shown to increase the survival of human ASCs, and the conditioned medium derived from hypoxiapreconditioned ASCs supported endothelial cell survival and endothelial tube formation.…”
Section: Discussion Of Findings and Relevant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have measured temperature of uv-irradiated skin from this viewpoint (Van der Leun 1966, Ramsay and Cripps 1970, Ramsay and Challoner 1976, Challoner and Woodrough 1978. As measurements were done several hours after exposure the temperature changes detected were really due to the ultraviolet erythema and not a consequence of the heat absorbed during the irradiation.…”
Section: Introductionmentioning
confidence: 99%